2022
DOI: 10.48550/arxiv.2203.08413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conductance Spectroscopy of Majorana Zero Modes in Superconductor-Magnetic Insulating Nanowire Hybrid Systems

Abstract: There has been a recent interest in superconductor-magnetic insulator hybrid Rashba nanowire setups for potentially hosting Majorana zero modes at smaller external Zeeman fields. Using the Keldysh non-equilibrium Green's function technique, we develop a detailed quantum transport approach that accounts for the hybrid structure comprising the Rashba nanowire coupled to the bilayer structure which includes the proximity inducing superconductor and the magnetic insulator. We provide a detailed analysis of three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Therefore, when the rotation rate of the one-dimensional helical chain is nonuniform, the above mapping is to an effective Hamiltonian that is reminiscent of a one-dimensional semiconductor nanowire with spatially varying parameters. Such nanowires have been considered extensively and it has been shown that trivial zero-energy Andreev bound states (ABSs) are abundant in these systems [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Theory Of a One-dimensional Spin Chain With Spatially Varyin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when the rotation rate of the one-dimensional helical chain is nonuniform, the above mapping is to an effective Hamiltonian that is reminiscent of a one-dimensional semiconductor nanowire with spatially varying parameters. Such nanowires have been considered extensively and it has been shown that trivial zero-energy Andreev bound states (ABSs) are abundant in these systems [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Theory Of a One-dimensional Spin Chain With Spatially Varyin...mentioning
confidence: 99%
“…In fact, it was shown that trivial Andreev bound states (ABSs) [49,50] are expected to be abundant in nanowires [38]. These trivial states can also result in zero-bias peaks which mimic MBSs and they occur, for instance, due nonuniformities in the nanowire parameters [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. Despite several further signatures of MBSs being proposed, due to the high prevalence of possible zero-energy modes, it remains unclear if a conclusive measurement of MBSs can be performed in nanowire systems.…”
Section: Introductionmentioning
confidence: 99%